Safety Efficiency of General Vaccination Against Hepatitis B in Urmia Dental Students: Vaccination and Hepatitis B - Seyyedi, Seyyed Amir; Asadollahi, Afsoon; Agha Mohammadi, Mehdi; Taram, Saman (Journal of Dental School, 2022)
Objectives Hepatitis B is a life-threatening disease that affects the liver. Despite the availability of vaccines and drugs, the disease remains a major human health problem worldwide. The aim of this study was to evaluate the serum level of anti-HBs in dental students of Urmia Dental School. Methods This descriptive study was performed on 72 (38 males, 34 females) dental students vaccinated against hepatitis B. Totally, 5 cc of venous blood was taken from each student and sent to a laboratory. In the laboratory, after serum separation, HBs antibody titer was measured by Bind Mono kit by ELISA. Data were analyzed using SPSS 21 by the Chi-square test. Results The minimum and maximum antibody titers were zero and 1000 IU/mg, respectively. Assessment of the frequency of HBs-Ab adequacy showed that 7 (9.7%) students had no immune response, 23 (31.9%) had low safety level, and 42 (58.3%) had good and acceptable safety levels. There was no significant difference between males and females in this regard (P>0.05).. Conclusion Most of the students were immune to the virus, although about 32% of them showed low immunity, indicating the need for re-vaccination. Seven out of 72 students were not immune to the disease.